Estrategia de fidelización de marca para productos agrícolas y su incidencia en el desarrollo local de mocache, año 2024 - Pillasagua Palma, Antonio Mauricio (2025)
This research analyzes brand loyalty strategies applied to agricultural products in the canton of Mocache, province of Los Ríos, Ecuador, and their impact on local development during 2024. In an agricultural environment characterized by growing competition and high quality demands, loyalty becomes a crucial tool for producers who seek not only to capture the attention of the consumer, but also to establish solid and lasting relationships. The study examines how Mocache farmers have implemented various marketing strategies to strengthen their brand and attract consumer loyalty. Key factors such as product quality, sustainability in agricultural practices and effective communication of brand values are investigated. Through surveys and interviews with farmers and consumers, we seek to understand perceptions about the brand and the reasons that influence consumer loyalty. Additionally, the impact of these strategies on local development is evaluated, considering economic and social aspects such as increased sales, job creation, and strengthening of the agricultural community. Challenges faced by producers, such as lack of resources and the need for marketing training, will also be addressed. Finally, the importance of strategic brand management that benefits farmers and contributes to the general well-being of the Mocache community is added.